IMPROVING THE ENGLISH SKILL OF PRIMARY TEACHERS THROUGH THE TOTAL PHYSICAL RESPONSE (TPR) METHOD - Ishak Ishak; Euis Yanah Mulyanah (JPSD (Jurnal Pendidikan Sekolah Dasar), 2019)
Abstract.This research aims to motivate and improve the English skill of Primary teachers in Tangerang, Indonesia. Quantitative is one approach that has chosen by the researcher with the quasi-experimental type and chooses the design of the nonequivalent control group. The researcher using experimental classes as trials and control classes as a comparison in applying the learning methods to determine comparative values between before and after given treatment by applying the Total Physical Response (TPR) method. The sample of this research was 40 teachers from two Primary Schools in Tangerang. The findings obtained a mean post-test value from the experimental class was 48.6. While the mean value after the test of the control class was 41.95, so there was the value of an increase of 6.65 or 0.16%. The hypothesis of the research stated that H0 is rejected and Ha is accepted, it means that there were very significant changes in increasing the mastery of English skills of Primary teachers by applying the TPR method. Keywords: english skills, primary school teachers, TPR